1974
DOI: 10.1002/1097-0142(197406)33:6<1615::aid-cncr2820330622>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's disease of the thymus gland

Abstract: Forty‐four patients with Hodgkin's disease that was initially limited to the anterior mediastinum were studied by clinicopathologic analysis. In about half the cases there was involvement of the thymus gland, and in the other half there was involvement only of the anterior mediastinal lymph nodes. Evidence is presented that the thymic lesion, often called “granulomatous thymoma”4 is in fact Hodgkin's disease of the thymus gland. All but 4 patients had the nodular‐sclerosis type of Hodgkin's disease, and in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…These include primary mediastinal tumors such as thymomas, germ cell tumors, and lymphomas. 1,[4][5][6]9,[11][12][13]15,18 In rare instances, metastatic Thymic Carcinoma Associated With MTC malignancy can be associated with MTC. 10 In addition, Suster et al 17 also described cases of MTC displaying an exuberant atypical epithelial proliferation of the lining epithelium reminiscent of the pseudoepitheliomatous hyperplasia in the skin or mucosal surfaces mimicking a malignant process.…”
Section: Discussionmentioning
confidence: 99%
“…These include primary mediastinal tumors such as thymomas, germ cell tumors, and lymphomas. 1,[4][5][6]9,[11][12][13]15,18 In rare instances, metastatic Thymic Carcinoma Associated With MTC malignancy can be associated with MTC. 10 In addition, Suster et al 17 also described cases of MTC displaying an exuberant atypical epithelial proliferation of the lining epithelium reminiscent of the pseudoepitheliomatous hyperplasia in the skin or mucosal surfaces mimicking a malignant process.…”
Section: Discussionmentioning
confidence: 99%
“…60 The identification of a population of scattered large B cells in T-cell-rich interfollicular zones raises the question of whether they give rise to any category of human lymphoma. A potential candidate is classical Hodgkin disease, a B-cell neoplasm 24,61 that tends preferentially to involve interfollicular T-cell areas in lymph nodes [62][63][64][65] and also the thymus, 63,66 where the morphologically similar asteroid B cells are 4 only a fraction of monocytoid B cells (26%) carry mutated IgH rearrangements, whereas the majority (74%) are unmutated. Other studies have identified only mutated immunoglobulin genes.…”
Section: Discussionmentioning
confidence: 99%
“…Mediastinal large B-cell lymphoma and classical Hodgkin's lymphoma both tend to affect younger adults, with some female preponderance, and to produce mediastinal neoplasms that are characterized by a prominent sclerosis. Hodgkin's lymphoma usually arises in lymph nodes but in the mediastinum, may arise in the thymus [69]. Mediastinal large B-cell lymphoma is composed of large atypical cells, some of which may resemble Reed-Sternberg cells, that usually lack immunoglobulin and that may express CD30.…”
Section: Primary Mediastinal (Thymic) Large B-cell Lymphomamentioning
confidence: 99%